Does the spin-off policy change the Shariah bank financial ratio? - Dina Fitrisia Septiarini, Miftahul Fahmi, (Opción, 2020)
This study aims to look for differences in financial ratios which include Capital Adequacy Ratio (CAR), Non Performing Finance (NPF), and Financing to Deposits Ratio (FDR) between before and after spin-off on Islamic banks in Indonesia. This study was a quantitative one. The data in this study were taken from 4 Shariah-based banks in Indonesia. The results of the statistical analysis of changes in the CAR, NPF, and FDR are more than 0.05, so the results are not significant. In conclusion, spin-off does not affect the decline in the performance of the financial performance of Islamic banks in Indonesia.